Publications in scientific journals by professors from Faculty of Stomatology in Universidad Peruana Cayetano Heredia, 2010-2019. - Mariño-Fierro, Genobeva Soledad (2022)
After the increase in scientific production in recent years, there aren’t reports of the profile of the publications made by the professors at the Faculty of Stomatology in Universidad Peruana Cayetano Heredia (FAEST-UPCH) in the last 10 years. Objective: Analyze the publications in scientific journals by professors at the Faculty of Stomatology in Universidad Peruana in the period 2010-2019. Material and methods: The research was of a retrospective, descriptive, cross-sectional, observational design; Scientific publications made by teachers from 2010-2019 were identified. The variables were sex, professional practice, academic department, employment status, teaching category, academic degree, second specialty, publications by teacher, type of publication, year of publication, internationally indexed journals, Scimago classification and WoS classification. The databases for the bibliographic search were Scielo, Pubmed, Google Scholar, Scopus and WoS; A descriptive and bivariate analysis was performed with the STATA v. 16.0. Results: It was found that 58.38% (n = 101) of the professors had at least one publication, 52.28% (n = 241) were original articles, 4.56% (n = 20) were indexed internationally, 20.00% (n = 4) had FI ≥2